1999
DOI: 10.1038/sj.bjp.0702348
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the prostanoid EP3‐receptor agonists M&B 28767 and GR 63799X on infarct size caused by regional myocardial ischaemia in the anaesthetized rat

Abstract: 1 This study investigates the eects of two agonists of the prostanoid EP 3 -receptor (M&B 28767 and GR 63799X) on the infarct size caused by regional myocardial ischaemia and reperfusion in the anaesthetized rat. 2 One hundred and sixty-seven, male Wistar rats were anaesthetized (thiopentone, 120 mg kg 71 , i.p.), ventilated (8 ± 10 ml kg 71 , 70 strokes min 71, inspiratory oxygen concentration: 30%; PEEP: 1 ± 2 mmHg) and subjected to occlusion of the left anterior descending coronary artery (LAD, for 7.5, 15,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 22 publications
1
27
0
Order By: Relevance
“…In the acute setting, the thermally damaged myocardium showed no structural changes by histology. The border zone between viable and irreversibly damaged myocardium can be delineated by fuchsin staining with high precision [22, 23]. We could confirm the high reproducibility of dimensions of the thermally damaged zone using of the temperature-controlled HF energy application mode, the dimensions of which were comparable to that found in a previous investigation for identical energy delivery [6].…”
Section: Discussionsupporting
confidence: 75%
“…In the acute setting, the thermally damaged myocardium showed no structural changes by histology. The border zone between viable and irreversibly damaged myocardium can be delineated by fuchsin staining with high precision [22, 23]. We could confirm the high reproducibility of dimensions of the thermally damaged zone using of the temperature-controlled HF energy application mode, the dimensions of which were comparable to that found in a previous investigation for identical energy delivery [6].…”
Section: Discussionsupporting
confidence: 75%
“…Previously, we have demonstrated that there is a significant increase in the levels of cTnT in the plasma within 3 hours after regional myocardial ischemia and reperfusion in the rat. 14 In cases of acute myocardial infarction in humans, cTnT levels in serum rise approximately 3 to 4 hours after the occurrence of cardiac symptoms and can remain elevated for up to 14 days. 18 It is interesting to speculate on the prospective mechanisms by which LPS causes a significant reduction in the degree of necrosis as demonstrated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…At the end of reperfusion, the hearts were cut into small pieces and incubated with p-nitroblue tetrazolium (0.5 mg⅐ml Ϫ1 for 20 min at 37°C). In the presence of intact dehydrogenase enzyme systems (normal myocardium), p-nitroblue tetrazolium forms a dark blue formazan, whereas areas of necrosis lack dehydrogenase activity and therefore do not stain (33,34). Infarct size is expressed as the percentage of the dry weight of the infarcted pieces over the total weight of the heart.…”
Section: No • Production By Rat Heartmentioning
confidence: 99%